Mikrouszkodzenia wysokotemperaturowych taśm nadprzewodnikowych drugiej generacji - Polegaj, Szymon; Wójcik, Mateusz; Nowak, Aleksander; Górny, Mikołaj; Pisarczyk, Joanna; Hajdasz, Sylwia; Szcześniak, Paweł
The phenomenon of superconductivity opens up wide possibilities for applications, particularly in medicine, industry, and power engineering. This article discusses superconducting technologies, focusing on second-generation high-temperature superconducting (2G HTS) tapes and their microstructure. 2G HTS tapes, based on the yttrium barium copper oxide (YBCO) superconductor, are manufactured using thin-film technology, and their production is continuously being improved. Microstructural studies of 2G HTS tapes were carried out using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS).
Keywords: nadprzewodnictwo; wysokotemperaturowe taśmy nadprzewodnikowe drugiej generacji; badania mikrostrukturalne; superconductivity; second-generation high-temperature superconducting tapes; microstructural analysis